Strabismus in Generations and Among Siblings - Shrestha, Sabina; Shrestha, Chunu; Manoranjan, Aparajita; Shrestha, Sushan Man (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Strabismus has been observed among family members in involved families. The study was conducted to document manifest strabismus running in generations and among siblings of strabismic patients. Methods: It was a hospital based prospective study conducted from May to November 2017. Strabismic patients with ocular deviation visiting Department of Paediatric Ophthalmology and strabismus were enrolled using specially designed proforma. Detailed ocular examinations were done and family history obtained regarding the presence of strabismus. Family tree was drawn for those with positive family history. Results: A total of 78 participants completed the study with 48.7% males. Family history of strabismus was present in 56.4%. Strabismus was present in two generations in 45.45%, in three generations in 18.2%, 1st and 3rd generation in 18.2%, 1st, 2nd and 4th generation in 4.5%  and among siblings only in 13.6%. Among those with positive family history, exotropia was present in 75% and esotropia in 25%. Among exotropes, manifest deviation was present in 47.7% and intermittent exotropia in 27.3%. Among esotropes, congenital esotropia was present in 9% and accommodative esotropia in 16%. First degree relatives were affected in 45.45% of strabismic patients among which 55% had manifest exotropia, 20% had intermittent exotropia, 15% had accommodative esotropia and 10% had congenital esotropia.Conclusions: Strabismus was found in different generations in 56.4% strabismic patients. Two generations were involved in 45.45%, three generations in 18.2%, 1st and 3rd generation in 18.2%, 1st, 2nd and 4th generation in 4.5% and siblings only in 13.6%. Genetic factors appear to be significant in strabismus in Nepalese population and it requires to be substantiated with further larger studies.